Research And Development For Capacity Building In TVET: The International PhD Programme Between UTHM And ITB Germany - M.Y., Jailani; W. A., Wan Mohd Rashid; H., Mohd Noor; A.M.D., Syarizul (Journal of Technical Education and Training, 2009)
The Ninth Malaysia Plan, which is one step on the way to achieve Vision 2020, features a separate section on Technical and Vocational Education and Training (TVET). It assigns responsibilities for TVET teacher education at the various levels to specific institutions such as polytechnics and community colleges. Malaysia will also face significant challenge as the country is set to become industrialized. Strategic knowledge and skill have to be the basic form of capital to position Malaysia towards industrialization. The education system especially in TVET must yield K-workers to push Malaysia into the K-economy. The Malaysian government has been dedicated to reform the education system and to place Malaysia into a world-class education hub. One critical strategy taken by the government is to implement the National Dual Training System (NDTS). Universiti Tun Hussein Onn Malaysia (UTHM) has been the key institution that strives to fulfil the national objective. UTHM offers and supply qualified TVET professionals at the academic levels of Bachelor, Master, and PhD programme to enrich the human capital of the nation. Due to the active international involvement and excellence recognition of UTHM as a TVET provider, a cross country research project involving UTHM from Malaysia, Universitat Autonoma de Barcelona (UAB) from Spain, The Institute Technik und Bildung (ITB), Universität Bremen from Germany and Vocational Education Development Centre (VEDC) Malang, Universitas Pendidikan Indonesia (UPI) Bandung and Technical Education Development Centre (TEDC) Bandung from Indonesia has agreed to partnership cooperation on a research project funded by the European Union Asia Link project headed by ITB. The research is focus on the development of trans-national standards of teacher training, their accreditation as well as the development of curricula. To strengthen the international collaboration, UTHM has taken an innovative initiative to work closely with the Universität Bremen from Germany to structure a German-Malaysian PhD programme. The cooperative program will facilitate the reorganization of Malaysia’s professional training scheme by benchmarking the German’s work-based TVET system. Currently, 18 candidates have already enrolled into the programme pursuing their doctorate academic advancement. As the Prime Minister of Malaysia put forward in his speech “We will need more thought-leaders, creators and innovators to achieve our aspirations”, this PhD graduates will definitely becoming the backbone to our NDTS transformation. The paper will highlight the existence, process and implementation of the innovative German-Malaysia Joint PhD programme.